0092 A Daytime Nap Restores Hippocampal Function and Improves Declarative Learning. (27th May 2020) - Ong, J; Lau, T; Lee, X; van Rijn, E; Chee, M W
Abstract: Introduction: Daytime naps have been shown to improve learning outcomes. One theory underlying enhanced encoding following a nap is via the synaptic downscaling of neurons potentiated during wake - a process facilitated by slow oscillations. In this study, we sought to investigate neural mechanisms underlying enhanced encoding following a nap compared to a waking period using a combination of PSG and fMRI methods. Methods: 40 healthy undergraduates (M=23.3y, SD=2.96y; 10 males) who slept normally the previous night encoded word pair lists across 2 runs in an MRI scanner at 1PM and 4.30PM. In between encoding sessions, participants either stayed awake and watched a documentary (Wake group; N=20), or napped for 90-min while undergoing polysomnography (Nap group; N=20). Approximately 40min after each encoding session, memory of these word lists were assessed in a cued-recall fashion. Performance in each session was measured by percentage of correct responses. Results: There were no baseline differences in encoding performance. However, a Session x Group interaction effect (p<0.001) was observed whereby performance significantly improved only in the Nap group in the second encoding session (Nap:20±19% vs. Wake:-1±13%). Concurrent to this, fMRI analyses revealed a Session x Run x Group interaction effect in the hippocampus (p=0.002) whereby hippocampal activation during encoding of the word lists increased only in the Nap group. In addition, although there was no association between degree of performance improvement in the nap group with duration of sleep or the various sleep stages (N1, N2, N3, REM), spindle count (12-15Hz) in the Nap group correlated significantly with both performance improvement (rs =0.46) and increase in hippocampal activation (rs =0.46). Conclusion: These results confirm the benefit of a nap on encoding processes. Hippocampal activation also increased following the nap, which could indicate renewed hippocampal capacity to store new information. While we hypothesized that slow wave sleep would aid in this transfer, we instead found a relationship between spindle count and both degree of performance improvement and increase in hippocampal activation. The interplay between NREM sleep oscillations, hippocampal downscaling and encoding performance could be more complex than originally thought. Support: National Medical Research Council, Singapore (NMRC/STaR/015/2013) and the Far East Organization.